STRATEGI COPING PENYINTAS BENCANA ALAM TSUNAMI ACEH 2004 YANG KEHILANGAN KELUARGA INTI - Nailul Falah (Republic of Indonesia Defense University, 2022)
This research was motivated by the many natural disasters that occurred in Indonesia. Natural disasters are events that have a major impact on the community where the natural disaster occurs. The impact that appears is quite complex, including the psychological impact on the survivors. These psychological problems that arise are very vulnerable to attack survivors, especially children who have lost their nuclear families due to natural disasters. After almost 18 years of the 2004 Aceh tsunami, child survivors who are currently growing into teenagers and early adults have managed to adapt to the existing conditions. Based on this background, this study aims to determine the methods of coping strategies for natural disaster survivors who have lost their nuclear family. This research uses a case study method with a qualitative approach. Data collection is done online using observation and interviews. The results of this study indicate that the methods of coping strategies used by two survivors of the 2004 Aceh tsunami who lost their nuclear family are emotion focused coping and problem focused coping. In emotion focused coping, the subject uses positive reappraisal, distancing, escape/avoidance, accepting responsibility and self controlling. While in problem focused coping, the subject uses planful problem solving and seeking social support.